The Implementation of Local Context Modules as an Effort for Disaster Risk Reduction (An Empirical Study in Disaster-Affected Schools) - Wahyono, U.; Kade, A.; Untara, K. A. A. (Jurnal Pendidikan IPA Indonesia, 2022)
The frequent increase of natural disasters enforces the need for disaster risk reduction implementation in education. This empirical study aims to determine the effectiveness of the module in the context of the Palu disaster threat in understanding the process of the earthquake, tsunami, liquefaction, and mitigation. This research was conducted in schools that were directly affected by the disaster. For those affected by the liquefaction, the research was carried out at SMP 21 Petobo. Then for those who were affected by the tsunami, the research was conducted at SMP 10 Kampung Lere, Palu. The results show that the students of disaster-affected schools already had initial knowledge regarding Disaster Risk Reduction before the module was implemented. Social media, mass media, and disaster locations contributed to the formation of their initial understanding. This study result indicates that the normal gain value for each disaster subject in disaster-affected schools increases. However, the normal gain for each topic affected by liquefaction is higher. The average increase in the normal gain of implementing modules in the school affected by liquefaction was 21.76 percent, and in the school affected by the tsunami was 10.49 percent.  The study concludes that understanding the local context disaster module is effective in disaster-affected schools and is more effective in schools that are heavily affected (liquefaction).